Pengaruh Penambahan Bayam terhadap Kualitas Mie Basah - Syamsul Arif, A.A. Putu Sri Mahayani Gatot Sargiman (AGROKNOW, 2014)
Abstract. Increasing one of [the] vegetable kind in noodle product at guess can increase fiber pregnancy. As known that tall fiber many implieds in vegetable. Spinach as one of [the] vegetable kind many grow in indonesia, very easy go at the price of many achievable. But has weakness that is when pass processing process not long. so that efforts to prolong spinach consumption time is need in penganekaragaman processing. Based on matters on, show author willing to increase product quality nie good in also nutrient.Â This watchfulness aims to detect influential spinach increasing level towards wet noodle quality. Watchfulness is carried out at Laboraturium Agriculture Faculty Of Technology Food Chemistry 17 Augusts 1945 Surabaya in September 2006. Watchfulness method that used in this watchfulness eksperimental, and use complete random plan (RAL), with 4 effort treatments is repeated 3 times so that total 12 sample with spinach increasing composition as follows : B0: Spinach 0%. B1: Spinach 12,5%. B2: Spinach: 25%. B3: Spinach 37,5%.Analysis result statistically in standard 0.05 and 0.01 in spinach increasing 0% (B0),12,5% (B1), 25% (B2), and 37,5% (B3) there water degree testing demoes influence difference existence very real (Frasio > Ftabel), in degree protein is demoing real influence difference inexistence (Frasio < Ftabel), in ash degree is demoing real influence difference existence (Frasio > Ftabel) . Spinach increasing 0% (B0), 12.5% (B1) 25% (B2), and 37,5% (B3) towards water degree demoes inclination increases, spinach increasing towards degree protein demo inclination decreaseds, spinach increasing towards ash degree demoes inclination decreaseds.A large part panelist declares to with wet noodle colour that is added spinach that is treatment B1 (spinach increasing 12,5%) gets prosetase lot from panelist (55%) and for taste declares out of conceit with treatment B2 (spinach increasing 25%) as much as 70% so much.Kata kunci : Mie basah , Bayam